Aligning Institutions and Incentives for Sustainable Water Supply and Sanitation Services - Mumssen, Yogita (World Bank, Washington, DC, 2018)
The objective of this study is to analyze how integrated policy, institutional, and regulatory interventions (institutional interventions in brief) can help align incentives for more sustainable water supply and sanitation (WSS) service delivery. The context for the study is the enhanced global concern about the sustainability of attempts to increase access to, and improve the quality of, WSS services, as exemplified in the sustainable development goals. Aligning institutional interventions refers to harmonization among the objectives for the sector, agreed principles established through political and social processes, and the organizations and mechanisms that implement actions based on such objectives and principles. This report focuses on the formal policy, institutional, and regulatory interventions available to and or prevalent in the water sector, recognizing the critical importance of the informal conventions that will be key factors in the success of any incentive regime. Previous global initiatives offered a range of promising technical solutions that often proved to be unsustainable. New thinking that draws not only infrastructure economics but also on the understanding of political, behavioral, and institutional economics is needed. This new thinking must be grounded within the differing contextual realities of countries globally and in lessons learned from what has or has not worked with regards to achieving specific objectives.